The Nuclear Magnetic Flowmeter for Monitoring the Consumption and Composition of Oil and Its Complex Mixtures in Real-Time - Davydov, Roman; Davydov, Vadim; Dudkin, Valentin (Energies (Basel), 2022)
The necessity of increasing the efficiency of primary oil purification in a drilling station or an offshore platform has been substantiated. We consider the problems that arise during the primary processing of oil mixtures. Important conditions for increasing the efficiency of primary purification (separation) of oil mixtures include measuring the consumption and determining the content of various impurities (water, undissolved particles) and air in them, with an error of no more than 2%. We analyzed the possibilities of using various designs of flowmeters to measure the consumption of the oil mixture coming from a well. It is also necessary to use other measuring instruments to control the state of this mixture, which creates additional problems (searching for an appropriate locations to place them, providing the required operating conditions). Various designs of nuclear magnetic flowmeters–relaxometers were considered, making it possible to measure the consumption of a liquid medium and its times of longitudinal T1 and transverse T2 relaxation with one device. The measured values of T1 and T2 determine the state of the medium. The design of the industrial nuclear magnetic flowmeter–relaxometer M-Phase 5000, which is used to control the flow and quality of oil and oil products, was considered in more detail. Problems were identified that did not allow using this design of a nuclear magnetic flowmeter–relaxometer in a drilling rig or offshore platform. A new design of a nuclear magnetic flowmeter–relaxometer was developed, implementing the methods for measuring q, T1, and T2. These methods and various technical solutions make it possible to use this device at a drilling station or offshore platform. The measurement errors of the consumption q, T1, and T2 were determined. The results of various media studies are presented and compared with q, T1, and T2 measurements on other devices and measured volume (to confirm the adequacy of q measurements). The application scopes of the developed nuclear magnetic flowmeter–relaxometer were determined, in addition to the systems of primary oil processing.